SPEECH STYLES USED BY THE JUDGES OF INDONESIAN IDOL 2012 - RIZKY, FINISHA PUTRI (Jurnal Ilmiah Mahasiswa FIB, 2013)
People need to communicate with other people to share their feeling, opinion, information, and etc. Here, people need language to communicate. In other words, language is the tool for communication. In this case, each person has his/her own way to deliver message. In communication, they can use some variations of language when they talk to other people. That is what we call it as style. Style can occur in written spoken discourse. The style that occurs in spoken discourse is called speech style. This study investigates the speech style produced by the judges of Indonesian Idol 2012 in giving comments to the finalists. In conducting the research, the writer analyzed three problems of the study which are: (1) What are the types of speech styles used by the judges of Indonesian Idol 2012? (2) What are the mostly used types of speech styles by the judges of Indonesian Idol 2012? (3) How do male and female judges speech styles differ? The main theory used in this study is by Joos (1961, cited in Brown and Attardo 2009) and supported by Chaer and Agustina (2010), Kridalaksana (1992), and Holmes (2001, cited in Abraham 2011).This study used qualitative document analysis since the writer tried to analyze the transcription of the judges’ utterances. The data of this study were the judges’ utterances in Indonesian Idol 2012 containing speech styles in Result and Reunion episode.The writer found that from 5 (five) types of speech styles (frozen style, casual style, consultative style, casual style, and intimate style) based on Joos’ theory, the writer only found 2 (two) of them. They were consultative style and casual style. The type of speech styles mostly used by the judges were consultative style in 43 (fourty three) utterances or 66,1% and followed by casual style in 22 (twenty two) utterances or 33,9%. The writer also found that male and female judges’ speech styles were not different because the writer found that both male and female judges mostly used consultative style in giving comments to the finalists.Finally, the writer suggests the next researchers to investigate the other kinds of speech styles which are influenced by social status, occasion, personal aim, and etc. The future researchers can also use other objects for their studies. Keywords: Speech style, Judges, Indonesian Idol 2012.